Consumers’ Buying Behavior Towards Online Shopping During The Covid-19 Pandemic: An Empirical Study In Malaysia - Nurul Sima Mohamad Shariff; Nur Hayani Izzati Abd Hamid (USIM Press, 2024)
The world has been affected by the COVID-19 outbreak recently, affecting the economy worldwide. Due to the booming of online activities, especially online shopping, this study is interested in finding the relationship between factors affecting consumers’ buying behavior on online shopping in Malaysia during the COVID-19 pandemic. The least studies related to this issue is needed in Malaysia to further understand the behavior of the consumers on online shopping. Based on available literatures, the factors of interest were trust, convenience, price, product variety and promotion on consumers’ buying behavior in Malaysia. The study employed survey procedures to collect the data, whereby online questionnaires were disseminated and recorded from a total of 335 respondents. The data was then analysed using several statistical analyses, namely pilot test, descriptive statistics and an ordered probit model. The result from an ordered probit model indicated that convenience, product variety, trust and promotion affected the Malaysian consumers’ buying behavior during the pandemic. Only price showed an insignificant impact on online shopping. This gave the sellers insight into understanding the consumers’ buying behavior on the online platform by planning marketing strategies to fascinate more customers.